AL-BADEE OF ABU AL-HASAN AL-HUSARI AL-QAYRAWANI IMPACT IN DEVELOPING OF THE ARGUMENTATION STUDY - Kouyate, Sekou (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2020)
ABSTRACT The research aims to reinterpret the well-known of Al-Badee Arts, in view of the Argumentation theory, in order to observe the transformations of the meaning in some models of Poetry of Abu Al-Hasan Al-Husari Al-Qayrawani. The researcher used the applied descriptive method, to study the ways of the transformations of the meaning, and extracting some models from the poems, and analyzing them. Therefore the research reached some important conclusions which are: If the new rhetoric is interested in the embellishment, because it is an Important instrument to the creativeness and the persuasion, Al-Badee can develop the Argumentation study, especially if the poet is sincere in his sufferance, and also wishes to convey his message, such as Al-Husari who benefited from Al-Badee Arts, for the purpose of persuasion, proof, and inference. The poet was able to combine between the form and content. His interests in Al-Badee Arts revealed his desire to remove dust from speech, and give it the complete clarification, customization and justification, etc., generally, his employment of Al-Badde fits the meaning he is trying to form. The repetition of the poet for some elements isn't a proof of inability to apply others elements, or a desire to decorate the speech only, but because he was bound by this repetition for its influential importance. Keywords: Al-Badee, Meaning, Argumentation theory.